Social inequity, taxes and welfare in Australasia. Issue 7 (16th September 2019) - Marriott, Lisa; Sim, Dalice
Abstract : Purpose: The purpose of this paper is to highlight, challenge and explain the inequitable treatment of tax and welfare fraudsters in the criminal justice systems of Australia and New Zealand. The authors offer prejudice by way of explanation and suggest that it is also prejudice that restricts the implementation of more equitable processes. A second objective of the study is to highlight the importance of critical tax research as an instrument to agitate for social change. Design/methodology/approach: A survey captures 3, 000 respondents' perceptions of the likelihood that different "types" of people will commit welfare or tax fraud. Using social dominance theory, the authors investigate the extent to which prejudice impacts on attitudes towards those engaged in these fraudulent activities. Findings: The authors find the presence of traditional stereotypes, such as the perception that businessmen are more likely to commit tax fraud and people receiving welfare assistance are more likely to commit fraud. The authors also find strong preferences towards respondents' own in-group, whereby businessmen, Maori and people receiving welfare assistance believed that their own group was less likely to commit either crime. Social implications: Where in-group preference exists among those who construct and enforce the rules relating to investigations, prosecutions and sentencing of tax and welfare fraud, it is perhaps unsurprising that welfare recipients attract less societal support than other groups who have support from their own in-groups that have greater power, resources and influence. Originality/value: The study highlights the difficulty of social change in the presence of strong in-group preference and prejudice. Cognisance of in-group preference is relevant to the accounting profession where elements of self-regulation remain. In-group preferences may impact on services provided, as well as professional development and education.